SPEAKING ASSESSMENT TECHNIQUES IN TEYL USING PROJECT-BASED LEARNING: A Descriptive Qualitative Research at One of Elementary Schools in Bandung - Maulida, Nazmi (2013)
This paper entitled "Speaking Assessment Techniques in TEYL using Project-Based Learning" is a descriptive qualitative research. This paper tries to find out various speaking assessment techniques used by the teachers who apply Project-Based Learning approach, the reasons for applying these assessment techniques, and the feedbacks given by the teachers. The framework of the assessment techniques were adopted from Georgiou (2003); Pinter (2006); and Cameron (2005) or alternative assessments of Project-Based Learning and the feedbacks were adopted from Cameron (2005:239). The data collection methods were used observation, Interview, and document analysis. The samples were three English teachers at one of elementary schools in Bandung. From the research findings, it is revealed that the teachers used four assessment techniques, namely projects, traditional-test, take-home task, and observation, and three feedbacks, namely corrective, evaluative, and strategic. From the findings it can be concluded that the assessment techniques and feedbacks helped the teachers to achieve the Project-Based Learning's goals. This paper recommends that teachers are suggested to apply suitable approach, activity, and assessment for students; the approach, activity, and assessment should be congruent with learning, children's needs and experience. Keywords: Speaking assessment techniques, young learners, Project-Based Learning, feedback. Skripsi yang berjudul "Speaking Assessment Techniques in TEYL using Project-Based Learning" adalah sebuah penelitian yang menggunakan metode deskriptif kualitatif. Skripsi ini mencoba untuk menemukan beberapa macam tehnik penilaian yang digunakan oleh beberapa guru yang menggunakan pendekatan Project-Based Learning, dengan alasannya, dan feedbacks yang digunakan para guru tersebut. Framework yang digunakan dalam assessment techniques diadopsi dari Georgiou (2003); Pinter (2006); and Cameron (2005) atau alternative assessments of Project-Based Learning, dan feedbacks yang diadopsi dari Cameron (2005:239). Metode pengumpulan data yang digunakan berupa observasi, interview, dan dokumen analisis. Objek penelitian dalam skripsi ini adalah tiga guru Bahasa Inggris di salah satu Sekolah Dasar di Bandung. Dari hasil penelitian didapat bahwa ketiga guru menggunakan empat jenis tehnik penilaian yakni; projects, traditional-test, take-home task, and observation, and three feedbacks, namely corrective, evaluative, and strategic. Dari hasil penelitian dapat disimpulkan bahwa tehnik penilaian dan feedbacks membantu guru-guru dalam mencapai tujuan Project-Based Learning. Skripsi ini merekomendasikan agar guru-guru Bahasa Inggris menggunakan pendekatan, aktivitas, dan penilaian yang tepat terhadap siswa; pendekatan, aktivitas, dan penilaian harus sejalan dengan pembelajaran, kebutuhan dan pengalaman siswa. . Keywords:Speaking assessment techniques, young learners, Project-Based Learning, feedback.